Intolerância religiosa e as novas perspectivas de criminalização - Pereira, Marcela da Silva (2024)
Religious intolerance, sometimes referred to as religious racism, particularly when directed against religions of African origin, constitutes a form of discrimination based on an individual's religion or beliefs. This issue is a growing concern in many societies worldwide. Legally, while some nations have laws that explicitly criminalize religious intolerance, others address this form of discrimination in a less comprehensive manner. Recently, despite increasing recognition of the need for broader laws to protect individuals from religious intolerance, certain legislations have not kept pace with this shift, leaving a concerning legal gap. It is crucial for le gal systems to adapt to social changes and acknowledge religious intolerance as a serious form of discrimination. In this context, this research provides a brief theoretical foundation and fosters a critical debate on the topic, demonstrates the legal principles involved in the matter, illustrates recent cases of religious discrimination in Brazil, presents current legislative proposals in the country, and outlines possible paths toward more stringent and comprehensive legislation